THE EFFECT OF STORYBOARD TECHNIQUE ON READING NARRATIVE TEXT ABILITY OF SECOND YEAR STUDENTS OF SMAN 9 PEKANBARU - Maulida, Firza Khaira; ', Eliwati; Sumbayak, Desri Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is an experimental research. The aim is to find the effect of Storyboard on reading narrative text ability of second year students of SMAN 9 Pekanbaru. The Population was 186 Science class students. The sample was XI Science 1 Class. The writer used cluster random sampling technique. The instrument of this research was try-out test, pre-test and post-test. The test had six texts and all questions were based on reading comprehension. There were 48 questions for each test. The writer used SPSS 17.00 Program to analyze the data. Try-out items were calculated by Microsoft-Excel 2010. In conclusion, there is significant effect of Storyboard Technique on reading narrative text ability of second year students of SMAN 9 Pekanbaru. It is suggested that this technique being applied not only in narrative text, some improvisations from further researcher are really needed to make this technique better than before.Key Words: Effect, Storyboard, Narrative Text, Ability